HOW THE EXTREME POOR COPE WITH CRISES: UNDERSTANDING THE ROLE OF ASSETS AND CONSUMPTION†. (November 2013) - Lawson, David; Kasirye, Ibrahim; Lawson, David; Amann, Edmund
Abstract This paper uses quantitative and qualitative panel household data, for the period 1992–2009, to model the coping mechanisms of households when faced with crises in Uganda. We find that socio‐economic determinants strongly influence coping mechanisms, with larger sized households being more likely to engage in the reduction of assets, and with households more likely to reduce food consumption when there is a drought and sell assets when faced with floods. Furthermore, being persistently poor and sick appear to result in disproportionately large reductions in assets over time—depleting a households asset base, and future coping mechanisms, of poorer households. Copyright © 2013 John Wiley & Sons, Ltd.